Reduced Height (Rht) Alleles Affect Wheat Grain Quality. - Richard Casebow; Caroline Hadley; Rajneet Uppal; Molla Addisu; Stefano Loddo; Ania Kowalski; Simon Griffiths; Mike Gooding (PLoS ONE)
The effects of dwarfing alleles (reduced height, Rht) in near isogenic lines on wheat grain quality are characterised in field experiments and related to effects on crop height, grain yield and GA-sensitivity. Alleles included those that conferred GA-insensitivity (Rht-B1b, Rht-B1c, Rht-D1b, Rht-D1c) as well as those that retained GA-sensitivity (rht(tall), Rht8, Rht8 + Ppd-D1a, Rht12). Full characterisation was facilitated by including factors with which the effects of Rht alleles are known to interact for grain yield (i.e. system, [conventional or organic]; tillage intensity [plough-based, minimum or zero]; nitrogen fertilizer level [0-450 kg N/ha]; and genetic backgrounds varying in height [cvs Maris Huntsman, Maris Widgeon, and Mercia]. Allele effects on mean grain weight and grain specific weight were positively associated with final crop height: dwarfing reduced these quality criteria irrespective of crop management or GA-sensitivity. In all but two experiments the effects of dwarfing alleles on grain nitrogen and sulphur concentrations were closely and negatively related to effects on grain yield, e.g. a quadratic relationship between grain yield and crop height manipulated by the GA-insensitive alleles was mirrored by quadratic relationships for nitrogen and sulphur concentrations: the highest yields and most dilute concentrations occurred around 80cm. In one of the two exceptional experiments the GA-insensitive Rht-B1b and Rht-B1c significantly (P<0.05) reduced grain nitrogen concentration in the absence of an effect on yield, and in the remaining experiment the GA-sensitive Rht8 significantly reduced both grain yield and grain nitrogen concentration simultaneously. When Rht alleles diluted grain nitrogen concentration, N:S ratios and SDS-sedimentation volumes were often improved. Hagberg falling number (HFN) was negatively related to crop height but benefits from dwarfing were only seen for GA-insensitive alleles. For HFN, therefore, there was the strongest evidence for a direct pleiotropic effect of GA-insensitivity, rather than an effect consequential to yield and/or height.